"After Ten Years" : Dietrich Bonhoeffer and Our Times - Bonhoeffer, Dietrich, 1906-1945 (Book collections on Project MUSE., 2017)
How does one read the signs of the times? What does it mean to resist? How do we engage faithfully in struggle? Dietrich Bonhoeffer has achieved iconic status as one who epitomizes what it means to struggle and resist tyranny and fascism and how one acts in faithful witness as a religious and political commitment. Bonhoeffer's witness and example is more relevant than ever. A testimony to that is a crucial essay penned by Bonhoeffer in 1942; "After Ten Years" is a succinct and sober reflection, and remains one of the best descriptions ever written about what happened to the German people under National Socialism. This volume presents this timely and unique essay in a fresh translation and a penetrating introduction and analysis of the importance of this essay-in Bonhoeffer's time and now in our own.